2019
DOI: 10.4103/ijnmr.ijnmr_205_18
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to medication and physical activity among people living with HIV/AIDS

Abstract: Background: The aim of this study was to investigate the adherence to medication and Physical Activity (PA) among People Living with HIV (PLHIV). Materials and Methods: In the present cross-sectional study, 122 PLHIV were selected. The research tools included the Baecke questionnaire and the AIDS Clinical Trials Group questionnaire. Data were analyzed by independent t test and multiple logistic regression. Results: The results of 7- and 30-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Age of antiretroviral therapy patients was a major determinant of lost to follow up, antiretroviral therapy patients were three times more likely to be missed from therapy in the age group of 15–24 years than patients over 45 years of age, this may be because those 15–24 years of age do not have a permanent job as much as most of the time they have a temporary address, this finding is consistent with the outcome of the study in Iran, 23 Ethiopia, 22 India, 18 Malawi. 17 …”
Section: Discussionsupporting
confidence: 84%
“…Age of antiretroviral therapy patients was a major determinant of lost to follow up, antiretroviral therapy patients were three times more likely to be missed from therapy in the age group of 15–24 years than patients over 45 years of age, this may be because those 15–24 years of age do not have a permanent job as much as most of the time they have a temporary address, this finding is consistent with the outcome of the study in Iran, 23 Ethiopia, 22 India, 18 Malawi. 17 …”
Section: Discussionsupporting
confidence: 84%
“…This finding suggested poorer antiretroviral adherence in PLWH, and supports previous reports that estimating adherence based on medication dose alone may overestimate the true adherence level. [49][50][51] Consequentially, a more appropriate measurement of adherence may need to consider all antiretroviral requirements including medication dose, schedule, and instruction. Older PLWH were observed to have better antiretroviral adherence compared to younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been a dramatic change in the coverage of ART services across the globe to include low- and middle-income countries, there are still challenges in helping patients to adhere to their initiated antiretroviral drugs. 6 Findings from North America showed that only 55% (n=17,573) of PLWHIV have an adherence level greater than 80%. In Africa, meta-analysis data showed that 77% of patients adhered to their medication, by considering an 80% cut-off value.…”
Section: Introductionmentioning
confidence: 99%